The effect of vitamin D on development of dento-alveolar structures of an albino mouse - Macasaet, Ma. Rita Celia C.; Tomacruz, Rachel C.
This experiment deals with the effect of Vitamin D deficiency on Dento-Alveolar structure. The diet of the albino mice were controlled and it was observed that deficiency in Vitamin D resulted to the following histologic observations : demineralization of osseus structures, disarray of bony matrix, vascular proliferation, and disorganized layering of dental lamina. Still birth and neonatal death also resulted due to deficiency in Vitamin D.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Vitamin D deficiency